Strategi Pengembangan Kemampuan Membaca Pemahaman Melalui Penerapan Keterampilan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Mutiara Wardifa Sari; Chandra Chandra; Salmaini Safitri Syam (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study focuses on the development of reading comprehension skills through the implementation of critical thinking strategies in Grade V elementary school students. Reading comprehension is not merely about decoding texts but involves understanding, interpreting, and analyzing the content. The integration of critical thinking aims to encourage students to become active readers who can question, evaluate, and make inferences based on the information they read. This research employs a qualitative descriptive approach by observing teaching practices and student responses in the classroom setting. Findings reveal that using critical thinking techniques—such as asking higher-order questions, making predictions, and drawing conclusions—helps students engage more deeply with the text. These strategies also improve their ability to connect prior knowledge with new information, fostering a more meaningful reading experience. Teachers play a vital role in guiding students to think reflectively and independently. The study concludes that consistent application of critical thinking in reading lessons significantly enhances students’ comprehension and supports the development of lifelong learning skills.